PENGEMBANGAN MODUL IPA SMP BERBASIS LITERASI SAINS PADA MATERI SISTEM EKSKRESI - Nandha Rahmasari; Maya Istyadji; Sauqina . (Jurnal Ilmiah Wahana Pendidikan, 2023)
An ideal IPA learning module should be able to train the science literacy skills of students, but in reality some outstanding IPA learning modules are still unable to train science literacy skills. The development of teaching materials in the form of science literacy-based modules is expected to make students accustomed to science literacy so as to improve the skills literacy science of students This module focuses on the material of the human excretion system. The purpose of this study is to describe the validity of junior high school IPA modules based on the literacy of material science human excretion systems. The development method used is 4D but in this study only used 3D. The data obtained comes from validation instruments. The validity result of the module obtained a percentage of 90.43% which means it is very valid. The average of 3.62 means very good. This module is also conducted reliability test with a percentage rate of 85.10%. Based on the results of the study, it can be concluded that the SMP IPA module based on science literacy in the excretion system material is suitable for use.